Microbiote shift in sequencing batch reactors in response to antimicrobial ZnO nanoparticles. Issue 111 (18th November 2016) - Liu, Zhenghui; Zhou, Huifang; Liu, Jiefeng; Yin, Xudong; Mao, Yufeng; Liu, Zhisen; Li, Zesheng; Xie, Wenyu
Abstract : Zinc oxide nanoparticles (ZnO NPs) have been monitored in wastewater treatment plants as their potential adverse effects on functional microorganisms have been causing increasing concern. Abstract : Zinc oxide nanoparticles (ZnO NPs) have been monitored in wastewater treatment plants as their potential adverse effects on functional microorganisms have been causing increasing concern. In this study, the effects of ZnO NPs on the microbial community and the characterization of resistant/sensitive genera to ZnO NPs toxicity were investigated in sequencing batch reactors. Our results showed that ZnO NPs induced a moderate decrease in COD and nitrogen and phosphorus removal under a mid-long-term exposure. The predominant bacterial phyla were Bacteroidetes and Proteobacteria . With an increase in ZnO concentrations, the proportion of Bacteroidetes decreased, whereas that of Proteobacteria increased. Further investigations indicated that Chryseobacterium and Dechloromonas exhibit high tolerance to ZnO NPs, whereas the genera Sediminibacterium and Blvii28 exhibit specific vulnerability to ZnO NPs.